Measurement and analysis of effective thermal conductivity of LaNi5 and its hydride under different gas atmospheres. (28th May 2021) - Yang, Yi; Mou, Xiaofeng; Zhu, Zezhi; Bao, Zewei
Abstract: In this work, an ETC measurement cell based on the steady-state radial heat flow method was fabricated, and its reliability was validated by a commercial instrument. The ETCs of unactuated and activated LaNi5 powder beds were measured under various filling gases in the pressure range from 0.1 to 1.5 MPa. The experimental results show that the ETC of activated LaNi5 powder is much lower than that of the unactuated material due to the pulverization effect. The ETCs of unactuated and activated LaNi5 powder in helium atmosphere lie in the ranges of 1.04–1.63 W m −1  K −1 and 0.49–0.85 W m −1  K −1, respectively. Furthermore, the ETC increases with the increasing pressure and thermal conductivity of filling gas. The effects of hydrogen absorption and desorption on the ETC were investigated by step-by-step reaction, which depend mainly on the hydrogen concentration and expansion/constriction of MH particles. Graphical abstract: Image 1 Highlights: A measuring cell for effective thermal conductivity of LaNi5 powder was built. Effect of filling gas pressure on effective thermal conductivity of LaNi5 was studied. Effective thermal conductivity of LaNi5 during absorption/desorption was studied. Effective thermal conductivity of LaNi5 rises with gas pressure and heat conductivity.